Essential Care Needs for Patients' Family Members at the Intensive Care Units in Palestine - Basma Salim Saleh Salameh; Sami Salim Saleh Basha; Linda Lee Eddy; Hiba Salem Judeh; Dalia Rahmi Toqan (Wolters Kluwer Medknow Publications, 2020)
Background: Understanding the needs of families of hospital patients, especially those in intensive care units is key to providing comprehensive, effective support. The aim of this study is to determine the needs of families of Intensive Care Unit (ICU) patients in four Palestinian hospitals. Materials and Methods: This was a cross-sectional, analytic study including 240 participants selected using convenience sampling. Data was obtained from participants from September 2016 to April 2018. The Critical Care Family Needs Inventory (CCFNI) was distributed to examine their needs. Descriptive analysis, t-tests, and Analysis of Variance (ANOVA) were conducted to analyze relationships between demographic characteristics of respondents and their needs. Differences were considered significant at p < 0.05. Results: The results revealed that the assurance domain was the most important, but participants had some unmet needs from the support domain. Parents reported higher levels of importance of all needs than other types of relatives of patients. In addition, participants with a higher level of education reported a significantly higher level of importance in the dimensions of assurance (F3,236= 2.85, p = 0.038), proximity (F3,236= 4.36, p = 0.006), and support (F3,236= 4.13, p = 0.007). Also, married participants had a higher need for all dimensions. Family members of patients who stayed more than 7 days had higher needs for support (F2,237= 3.39, p = 0.035) and comfort (F2,237= 3.92, p = 0.021). Conclusions: Family members of ICU patients have certain unmet needs, which require attention from healthcare professionals and administration in Palestinian hospitals. In addition, sociodemographic variables influence family member needs.